Conceptualization and Reflection on Educational Practice in a Continuing Education In-Service Training Program For Teachers Of Higher Secondary Education In Mexico - Nava-Gómez, Guadalupe Nancy (2014)
This article presents an approach toward the conceptualization of the educational practice in an in-service teaching program in the Autonomous University of the State of Mexico (UAEM).  After establishing the difference between initial and continuous educational programs, the problems about the current in-service teaching preparation programs oriented to prepare in-service teachers of higher secondary education are described.  The aim of this paper consists of presenting pedagogical experiences of a continuous in-service teaching program whose objective is the professionalization of the teaching and educational practice based on the reconceptualization of it. Aspects such as the teacher updating, educational quality and permanent education are widely discussed from the current educational reforms in Mexico within a critical pedagogical framework.  As a result, it is pointed out that Mexico requires promoting educational programs of higher education oriented to the professionalization of the educational practice. Additionally, it is argued that in-service teacher preparation must leave behind traditional practices such as short courses, workshops and seminars in order to enhance the continuous and permanent education of those teachers working at the higher secondary level.